SISTEM PENDETEKSIAN PENYUSUPAN JARINGAN KOMPUTER DENGAN ACTIVE RESPONSE MENGGUNAKAN METODE HYBRID INTRUSION DETECTION, SIGNATURES DAN ANOMALY DETECTION - Novriyanto Novriyanto; Haris Simare Mare; Wenni Syafitri (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2011)
The progress of internet technology increase the need of security data. The progress of tools which have intrusion ability, also influence these needed. The methods of Intrusion Detection System (IDS)  implementation and methods of analyze intrusion have excess and lack, which mutually completes. There are a lot of IDS now, but just an IDS open source based is snort. Method of snort implementation is network based restricted. This Final Task’s system used Hybrid Intrusion Detection System, Signatures and Anomaly Detection Methods. The indicator which used to detect intrusion are IP Address and Port Number. This system use TCP, UDP and ICMP protocols. This system also, is completed by active response, like blocking access for intruder. This System Implementation with Java Programming Language for engine perform and Java Server Pages (JSP) to develop user interface, The database which used is MYSQL. There are two of development test; Link system test and intrusion test. The link system test show the connect each interface. Intrusion is  executed by host detection which used DoS HTTP tools and network detection which used Ping of Death’s scripts. The intrusion testing conclusions are; can be detected, analyze and active response for intrusion.